Можливості оптимізації лікування дифузного токсичного зоба шляхом корекції функціональних порушень печінки - Свистун, І. І. (Clinical Endocrinology and Endocrine Surgery, 2011)
The effect of α-lipoic acid on functional liver changes of patients with a diffuse toxic goiter during the month was studied. Positive influence on the indices of aminotranferases, bilirubine, alkaline phosphatase, total protein and also reduction of oxidative stress and decreased of endogenous intoxication level were shown that allows to recommend lipoic acid as as an adjuvant in the treatment of patients with diffuse toxic goiter.